(untitled) (Applied Biological Research, 2026)
Zinc is an essential micronutrient vital for various physiological processes in plants; however, its narrow gap between deficiency and toxicity demands careful nutrient management. This study assessed the impact of zinc (zinc sulphate heptahydrate @ 0.0–15.0 mM L⁻¹) on the composition of chloroplast pigments and anti-oxidative enzyme activities within the chloroplasts of acid lime (Citrus aurantiifolia Swingle) leaves over two consecutive years.Moderate zinc concentrations (7.5–10.0 mM L⁻¹) significantly improved chlorophyll (a, b and total), carotenoids, xanthophylls and plastoquinone contents, indicating enhanced chloroplast development and improved photosynthetic capacity. Rubisco activity, a key enzyme involved in carbon fixation, was highest at 10.0 mM L⁻¹ zinc.In contrast, both zinc deficiency (0.0 mM L⁻¹) and zinc toxicity (≥12.5 mM L⁻¹) caused a significant reduction in pigment levels and Rubisco activity, which was associated with increased oxidative stress. Activities of superoxide dismutase, glutathione, and ascorbate peroxidase in the chloroplasts increased under these stress conditions, reflecting the activation of antioxidant defense mechanisms.This biphasic response demonstrates the dual role of zinc in plant metabolism—supporting physiological balance at optimal concentrations while inducing oxidative stress and metabolic disruption under deficiency or excess. The study highlights the importance of maintaining a critical zinc threshold to sustain photosynthetic efficiency and redox balance in acid lime.